Specificity and mechanism of protein kinase C activation by sn-1,2-diacylglycerols. - Ganong, B R (1986)
The specificity of protein kinase C activation by sn-1,2-diacylglycerols and analogues was investigated by using a Triton X-100 mixed micellar assay [Hannun, Y. A., Loomis, C. R. & Bell, R. M. (1985) J. Biol. Chem. 260, 10039-10043]. Analogues containing acyl or alkyl chains eight carbons in length were synthesized because sn-1,2-dioctanoylglycerol is an effective cell-permeant activator of protein kinase C. These analogues were tested as activators and antagonists of rat brain protein kinase C to determine the exact structural features important for activity. The analogues established that activation of protein kinase C by diacylglycerols is highly specific. Several analogues established that both carbonyl moieties of the oxygen esters are required for maximal activity and that the 3-hydroxyl moiety is also required. None of the analogues were antagonists. These data, combined with previous investigations, permitted formulation of a model of protein kinase C activation. A three-point attachment of sn-1,2-diacylglycerol to the surface-bound protein kinase C-phosphatidylserine-Ca2+ complex is envisioned to cause activation. Direct ligation of diacylglycerol to Ca2+ is proposed to be an essential step in the mechanism of activation of protein kinase C.